The Effect of Administering Goat Manure and Green Tonic Fertilizier on the Growth and Yield of Pagoda Mustroper Plants (Brassica narinosa L.): Pengaruh Pemberian Pupuk Kandang Kambing dan Pupuk Green Tonik Terhadap Pertumbuhan dan Hasil Tanaman Sawi Pagoda (Brassica Narinosa L.) - Wahyu; Yasin, Usman; Suryadi; Podesta, Fiana; Fitriani, Dwi (Nabatia, 2024)
This study aims to determine the effect of goat manure and green tonik fertilizer on the growth and yield of pagoda mustard (Brassica Narinosa, L). The design used was a factorial completely randomized design (CRD) with 2 factors. the first factor of goat manure with doseges (P): P0 (standard N, P and K), P1 (10 tons/ha), P2 (15 tons/ha), P3 (20 tons/ha). the second factor was the concentration of green tonic K1 (1 ml/l), K2 (2 ml/l), K3 (3 ml/l), with each treatment repeated 3 times. Data were analyzed using analysis of variance (ANOVA) and if significantly different, further testing was done using Duncan's Multiple Range Test (DMRT) at a 5% level. The results showed that goat manure significant effected plant height (14 dap, 21 dap, 28 dap), number of leaves (14 dap, 21 dap), canopy area (7 dap, 21 dap, 28 dap), fresh weight of plant, and root length. Goat manure can meet the needs of N, P and K. The concentration of goat manure has significantly effected plant height at 28 dap and fresh weight of plants. There was an interaction between goat manure and green tonik fertilizer on the parameter of plant height at 28 dap.